Image and Object Recognition System Apps for Kids Learning - Nor Muhammad Wafiz Hamka Noruddin,; Muhammad Anas Bin Razali, (Evolution in Electrical and Electronic Engineering, 2021)
Deep learning is an artificial intelligence branch utilizing deep neural network systems that are highly specialized in machine vision, voice recognition, natural language, and other areas. Google has launched TensorFlow, a deep learning software library for open source definition, training, and implementation of Models in November 2015. In recent years, deep learning technology has developed significantly. Deep learning and object recognition is the use of artificial intelligence (AI) on recognizing obstacles, object identifying, and even traffic lights to improve quality in the processing system. The use of AI eliminates the need for human work in the sectors. This project is developed using AI to acts as a helper for parents and teachers to develop kids' growth. Tensorflow is implemented into this project to detect, training and process the object that it sees. Furthermore, Google Collab is used as a processing cloud because of its free cloud GPU usage. Finally, Android Studio is used to build the Android Application Package (APK) for the phone.